Single R Gene Introgression Lines for Accurate Dissection of the Brassica - Leptosphaeria Pathosystem - Larkan, Nicholas J.; Yu, Fengqun; Lydiate, Derek J.; Rimmer, S. Roger; Borhan, M. Hossein (Frontiers in Plant Science, 2016)
Seven blackleg resistance (R) genes (Rlm1, Rlm2, Rlm3, Rlm4, LepR1, LepR2 & LepR3) were each introgressed into a common susceptible B. napus doubled-haploid (DH) line through reciprocal back-crossing, producing single-R gene introgression lines (ILs) for use in the pathological and molecular study of Brassica – Leptosphaeria interactions. The genomic positions of the R genes were defined through molecular mapping and analysis with transgenic L. maculans isolates was used to confirm the identity of the introgressed genes where possible. Using L. maculans isolates of contrasting avirulence gene (Avr) profiles, we preformed extensive differential pathology for phenotypic comparison of the ILs to other B. napus varieties, demonstrating the ILs can provide for the accurate assessment of Avr - R gene interactions by avoiding non-Avr dependant alterations to resistance responses which can occur in some commonly used B. napus varieties. Whole-genome SNP-based assessment allowed us to define the donor parent introgressions in each IL and provide a strong basis for comparative molecular dissection of the pathosystem.